2016
DOI: 10.1116/1.4964749
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydrogenated diamondlike carbon thin films using neon–acetylene based high power impulse magnetron sputtering discharges

Abstract: Hydrogenated diamondlike carbon (DLC:H) thin films exhibit many interesting properties that can be tailored by controlling the composition and energy of the vapor fluxes used for their synthesis. This control can be facilitated by high electron density and/or high electron temperature plasmas that allow one to effectively tune the gas and surface chemistry during film growth, as well as the degree of ionization of the film forming species. The authors have recently demonstrated by adding Ne in an Ar-C high pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The H content of the coatings measured by ERDA correlates with the deposition rate, Figure 6. The H concentration remained low, below 8%, but it could still have decreased the film hardness, as previously described in [25]. The hardness of films deposited on Si samples is also shown in Figure 6 as a function of deposition process.…”
Section: Characterization Thin Film Deposited On Si Substratesupporting
confidence: 73%
See 2 more Smart Citations
“…The H content of the coatings measured by ERDA correlates with the deposition rate, Figure 6. The H concentration remained low, below 8%, but it could still have decreased the film hardness, as previously described in [25]. The hardness of films deposited on Si samples is also shown in Figure 6 as a function of deposition process.…”
Section: Characterization Thin Film Deposited On Si Substratesupporting
confidence: 73%
“…The increased ionization provided by HiPIMS is beneficial also in reactive deposition of DLC. The use of a reactive environment by the addition of acetylene, to either Ar, Ar/Ne or Ne environment was demonstrated in obtaining hydrogenated DLC coatings with low hydrogen content, with hydrogen contents up to 15%-20% [10,25]. In that case, the HiPIMS plasma activates the reactive gas precursor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study with rather high frequency (250 Hz to 1 kHz), the plasma was found to have larger ionized species yielding enhance densification with larger sp 3 fraction [9]. In more recent, works Ar and C 2 H 2 gas mixture were used to deposit a-C films but films were not H free [13,14]. Clearly, HiPIMS offers possibilities to deposit carbon thin films with high density and high sp 3 fractions, and more systematic studies are required to achieve this.…”
Section: Introductionmentioning
confidence: 98%
“…[135][136][137] They have been used as the carbon source for SiCN films, where N 2 was used to supply nitrogen, resulting in a complex sputtering process with more than one reactive gas. [58,60] Several electron impact reactions are possible for the C 2 H 2 molecule.…”
Section: Acetylenementioning
confidence: 99%